TRANSFORMASI SOSIAL MAJELIS RATIB AL-‘ATTAS HABIB MUHAMMAD AL-HABSYI GRESIK - Muhamad Mustofa Ludfi; Shofwan Aljauhari (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
This research explores the social transformation occurring within the Majelis Ratib al-‘Attas Habib Muhammad al-Habsyi Gresik. This research focuses on three aspects: the concept and nature of egalitarianism applied in the assembly to all its members, the social impact of the assembly on the lives of its members, and the existence of the assembly in the flow of changes in social life. This research uses a phenomenological approach with Moustakas' (1994) phenomenological data analysis, namely Bracketing, Reduction, Clustering, and Validation (confirming the theme through data triangulation). The researcher used a questionnaire with 50 randomly selected respondents, all of whom were council members, and conducted ethnographic interviews based on the James P. Spradley model. Primary sources are one of the strengths of this research. The research results show that this assembly is agreed upon by the majority of respondents as an assembly that highly emphasizes the principle of equality. (egaliterisme). Respondents also gave a high score to the assembly's ability to change the social lives of its members. Meanwhile, regarding the existence of the assembly, respondents still believe that the Ras assembly is capable of enduring the social changes occurring within the community. Thus, this study is expected to become a comprehensive repository on the philanthropy of a congregation that dares to take unpopular steps amidst other more established congregations.